PENERAPAN MODEL PEMBELAJARAN CTL UNTUK MENINGKATKAN HASIL BELAJAR PPKn SISWA KELAS VIII SMP NEGERI 2 TELUK KUANTAN - Yunelmi Yunelmi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is motivated by the low student learning outcomes of PPKn, the low student learning outcomes ofPPKn can be seen from the average student learning outcomes that is 58.26 and from 24 students only 13students achieve KKM. This study aims to improve student learning outcomes through the application of CTLlearning models. This research is a classroom action research, conducted at SMP Negeri 2 Teluk Kuantan. Theresearch subjects were eighth grade students with 24 students. The data used in this study is data on studentlearning outcomes. The results showed that after the CTL learning model was applied the learning outcomes hadincreased. In the pre-cycle average student learning outcomes were 58.26 increased in cycle I with an averagescore of 69.76 and increased again in cycle II with an average score of 81.46. In addition the number of studentswho reached the KKM also experienced an increase in the pre cycle the number of students who completed were13 students, in the first cycle increased by the number of 18 and in the second cycle increased to 21 students.Therefore, it can be concluded that the CTL learning model can improve the PPKn learning outcomes of theeighth grade students of SMP Negeri 2 Teluk Kuantan.